Multielemental Stoichiometry in Plant Organs: A Case Study With the Alpine Herb Gentiana rigescens Across Southwest China - Zhang, Ji; Wang, Yuanzhong; Cai, Chuantao (Frontiers in Plant Science, 2020)
Multiple elements are required to be allocated to different organs to meet the demands for plant growth, reproduction, and maintenance. However, our knowledge remains limited on the stoichiometry in all plant organs in response to heterogeneous environments. Here we present the systematic investigation of multi-elemental stoichiometry in organs of the alpine plant Gentiana rigescens across different environmental conditions. The slopes of N–P stoichiometric relationships amongst organs in G. rigescens did not differ significantly between environments even in flowers, the most active organ with the highest N and P level. C:P ratios had strong positive relationships with N:P ratios within and between organs. Zn had strong positive correlations with Fe, S, or Cu in each organ, indicating the potential interactions among the homeostases of these elements. The contents of macroelements, such as C, N, P, Ca, Mg, and S, were higher in plant organs than those in soil and exhibited a relatively narrow range in plant organs. However, G. rigescens reduced Fe uptake from soil and showed the strictest homeostasis in its root, implying its resistance to excess Fe. Furthermore, precipitation and temperature associated with geography, followed by soil P, were the main divers for the multi-elemental stoichiometry in this species. Plant stoichiometry responded differently to abiotic environmental factors, depending on organ type and element. N:P ratio, no matter in which organ, showed little flexibility to climate factors. The results have implications for understanding the regulation of multi-elemental stoichiometry in plant individuals to environmental changes. Further studies are needed on the interactions of multi-element homeostasis in plants.